2020
DOI: 10.15244/pjoes/109492
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selenium Deficiency in the Environment on Antioxidant Systems of Wumen Semi-Fine Wool Sheep

Abstract: The Wumeng semi-fine wool sheep industry is the pillar industry in the Wumeng mountainous area. The objective of this study was to explore the effects of selenium deficiency in the environment on the mineral element metabolism and antioxidant system function in grazing Wumen semi-fine wool sheep, and provide scientific and objective data for the reference of the development of Wumen sheep industry. Samples of soil and forage were collected from affected and unaffected areas. Samples of tissue and blood were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Clinically the mineral deficient group had weakness, emaciation, retardation of growth, change wool color, easily detached wool, partial alopecia and pale mucous membrane, according to a clinical examination. The aforementioned clinical indicators were additionally detailed by [8,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically the mineral deficient group had weakness, emaciation, retardation of growth, change wool color, easily detached wool, partial alopecia and pale mucous membrane, according to a clinical examination. The aforementioned clinical indicators were additionally detailed by [8,35].…”
Section: Discussionmentioning
confidence: 99%
“…Two molecules of hydrogen peroxide are broken down by catalase into one oxygen molecule [46]. The GSH-Px active site contains selenium, which is essential for catalyzing the reduction of hydrogen peroxide and other organic peroxides GSH-Px activity [35]. Zinc activates glutathione peroxidase, converting glutathione into oxidized form.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, molecular structure of S element and Se element are similar, and competing the same absorbing sites of the plant roots in soil solution [48]. The decreasing content of the soluble S, resulting in an increasing absorption of Se nutrition, and increasing contents of Se in the forage [49,50].…”
Section: Effects Of Nano-k 2 Moo 4 On Nutrition Values Of Forage From...mentioning
confidence: 99%
“…However, the excessive content can cause very large harm to the organisms. The heavy metal accumulate in the soil will remarkably decrease the quality and production of forage [21,22]. It has been reported that heavy metal reduced gastrointestinal peristalsis, while lead to a strong stimulation of the gastrointestinal mucosa and caused gastroenteritis anorexia, which bring the decrease of daily gain, slaughter rate, and daily feed intake [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Severe affected Wumeng sheep included permanent recumbency and eventual death. Many scholars have studied animal mineral deficiencies in the whole world [4,5]. Huang (2002) reported sulfur (S) deficiency in Tibet sheep and goats causing by low S content in soil and forage in pasture in Gansu Province in the Northwest China [6].…”
Section: Introductionmentioning
confidence: 99%